Glacial dispersal and flow history, East Arm area of Great Slave Lake, NWT, Canada. (1st June 2017) - Sharpe, D.R.; Kjarsgaard, B.A.; Knight, R.D.; Russell, H.A.J.; Kerr, D.E.
Abstract: Little work has been completed on paleo-ice-sheet flow indicators of the Laurentide Ice Sheet, west of the Keewatin Ice Divide. Field mapping, sampling and analysis of glaciogenic sediment (∼500 sample sites) in a ∼33, 000 km 2 region near the East Arm of Great Slave Lake in northwestern Canada, provided a rare opportunity to improve understanding of sediment erosion and transport patterns. Glacially-eroded bedrock and sedimentary landforms record east to west flow with NW and SW divergence, mapped within a portion of the Great Slave Lake flow tract. Transported till reflects a similar divergent flow pattern based on dispersal geometries for multiple indicators (e.g., heavy minerals and lithic fragments), which are aligned with the dominant and latest ice flow direction. Glaciofluvial erosion (e.g., s-forms and till removal), transport, and deposition (mainly as esker sediment) are set within 0.3–3 km wide meltwater erosional corridors, spaced regularly at 10–15 km intervals. Transport paths and distances are comparable in till and esker sediment, however, distances appear to be greater (∼5–25 km) in some esker constituents and indicator minerals are typically more concentrated in esker sediment than in till. Corridors form a divergent array identical to the pattern of ice-flow features. The congruence of ice and meltwater flow features is interpreted to be a response to a similar ice sheet gradient, and close timing of events (late dominant glacial ice flow and meltwater flow). The similarity in glacial and glaciofluvial flow patterns has important ramifications for event reconstruction and for exploration geologists utilizing mineral and geochemical tracing methods in this region, and possibly other parts of northern Canada. The correspondence between East Arm dispersal patterns, landforms and flow indicators supports interpretation of a simple and predictable single flow divergence model. This is in contrast to previous, multi-flow models, in which fan-shaped geometries are often reported to result from multiple transport events, compared to single-flow divergence. The observed widespread effects of glaciofluvial processes (e.g., erosional corridors) indicate a need to update existing terrain process models. Highlights: Glacial and glaciofluvial landform and sediment transport data portray a simple regional divergent flow pattern. This simple pattern contradicts inferred flow complexity down flow of Keewatin and McClintock Ice Divides. Western Keewatin glacial terrain is an erosional landscape highlighted by glaciofluvial corridors. Erodible Thelon sandstone clasts were transported >100 km at ∼50% concentration. Mineral tracing should focus on transport data rather than inferred flow complexity based on striae data.